Bases to determine Qualit standards in the development of the Physical Education.: Offer of Management, one before and one later, to the development of a mega event (Revista Educación Física Chile, 2022)
The article provides background giving rent to lay the foundations on which have been taken into account when addressing the development of a mega sport, meaning that this particular look, before assuming his organization, should consider other important elements in effect for a selective basis wider stakeholders, but from an improved quality of physical education developed at the base, as are the schools. This is providing the background to the development of sports should be, assuming the point of view constructive criticism, the implementation of aspects such as diagnostics, infrastructure analysis, determination of sporting interests, establishment of institutions for the development and promotion of sport, determination of levels of knowledge of key aspects of plans and studies in education, provision of adequate channels for participation at the grassroots level, school, among others. All aspects and aimed at determining the quality and thus the amount of physical education and sport, in this way to assume greater organizational challenges.